Chicken Sausage Production Process at PT. X: Proses Produksi Sosis Ayam di PT. X - Kiranti, Irma; Hudi, Lukman; Pradiko, Rifky (Procedia of Engineering and Life Science, 2024)
This study investigated the chicken sausage production process and explored problem-solving strategies using fishbone diagrams. The analysis identified key stages, including raw material preparation, grinding, mixing, molding, cooking, cooling, cutting, and packaging. Fishbone diagrams were employed to systematically dissect process issues, revealing root causes related to personnel, methods, machines, materials, and environment. The findings highlight the effectiveness of fishbone diagrams for identifying and addressing production bottlenecks, paving the way for optimized efficiency and quality control in sausage manufacturing. Highlights : Process breakdown: The study identified key stages in chicken sausage production (preparation, grinding, mixing, etc.) using fishbone diagrams. Root cause analysis: Fishbone diagrams helped pinpoint root causes of process issues across various factors (personnel, methods, machines, etc.). Quality improvement: The findings suggest fishbone diagrams as an effective tool for identifying and addressing bottlenecks, leading to optimized efficiency and quality control. Keywords: chicken sausage, production process, fishbone diagrams, problem-solving, quality control